A Review on the Demand status and Strategies for Conservation of Brihad Panchamoola Species - R, Kalaiselvi; Jose, Judin; S, Mohana Priya; R, Muthumari; S, Gokul Krishnan; Warrier, Rekha R (Indian Forester, 2022)
The Indian Systems of Medicine has a long tradition of using medicinal plants. Various parts, such as roots, bark and leaves, are harvested, processed and used to prepare herbal formulations. Dasamoola, one such herbal formulation consumed for general health improvement, uses roots of five medicinal trees, Aegle marmelos, Premna integrifolia, Oroxylum indicum, Stereospermum suaveolens, Gmelina arborea. As the root is the major constituent of the formulation, the five species are destructively harvested from wild, leading to depletion of their genetic stocks. This commercial exploitation has pushed the species to threatened levels in the wild, as reported through CAMP Workshops. The increasing demand for the formulation and the widening demand and supply gap for raw materials has encouraged research on various aspects of these five species. The paper describes the demand of the species both at industry and household levels, leading to their threatened status, there is need for research to conserve the resources and strategies for sustainable use.